Factors Affecting Job Satisfaction of Members of the Family Empowerment and Welfare Movement Team (TP PKK) in Ponorogo Regency - Putri, Puspa Buana; Mokhamad Natsir; Harianto Respati (Journal of Scientific Insights, 2025)
This study aims to analyze the factors that influence job satisfaction of members of the Team for Empowerment and Family Welfare (TP-PKK) in Ponorogo Regency. The factors examined in this study include appropriate rewards, work environment conditions, and coworker support, which are assumed to have an influence on job satisfaction. Job satisfaction is a crucial aspect in maintaining organizational performance and stability, especially in the context of social-based organizations such as TP-PKK, which depends on the dedication and active participation of their members. The research method used is explanatory quantitative, with statistical analysis techniques to test the causal relationship between variables. Data were collected through questionnaires distributed to TP-PKK members in Ponorogo Regency and analyzed using multiple linear regression techniques. The results showed that appropriate rewards, work environment conditions, and coworker support had a significant effect on job satisfaction. Rewards that are fair and in line with members' contributions increase work motivation, while a conducive work environment creates an atmosphere that supports productivity. In addition, support from colleagues plays an important role in building positive social interactions, increasing the sense of attachment to the organization.